2017
DOI: 10.12659/msmbr.903518
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Evaluation of New Immunoregulatory Genes in Mesenchymal Stromal Cells of Different Origins: Comparison of Normal and Inflammatory Conditions

Abstract: BackgroundMesenchymal stromal cells (MSCs) possess potent immunomodulatory properties that increase their value as a cell-based therapeutic tool for managing various immune-based disorders. Over the past years, accumulated results from trials using MSCs-based therapy have shown substantial contradictions. Although the reasons underlying these discrepancies are still not completely understood, it is well known that the immunomodulatory activities mediated by distinct MSCs differ in a manner dependent on their t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Our work showed that these downregulated DEmRNAs can be regulated by lncRNAs AC147651.1 and AC111000.4 in cis-and transregulation manners. Hence, we can conclude that lncRNAs What is more, IDO1 [28] and SEMA7A [29] were reported to be important in the immunomodulatory effect of mesenchymal stromal cells in acquired AA. In our study, IDO1 and SEMA7A were downregulated and they were shown to be cis-and trans-regulated by lncRNAs AC007991.2 and RHOXF1P1.…”
Section: Discussionmentioning
confidence: 74%
“…Our work showed that these downregulated DEmRNAs can be regulated by lncRNAs AC147651.1 and AC111000.4 in cis-and transregulation manners. Hence, we can conclude that lncRNAs What is more, IDO1 [28] and SEMA7A [29] were reported to be important in the immunomodulatory effect of mesenchymal stromal cells in acquired AA. In our study, IDO1 and SEMA7A were downregulated and they were shown to be cis-and trans-regulated by lncRNAs AC007991.2 and RHOXF1P1.…”
Section: Discussionmentioning
confidence: 74%
“…FGL2 is primarily bound to FcgR, including FcgRIIB and FcgRIII [44]. By a previous report, FGL2 mRNA expression was upregulated in human ADSCs with a cocktail of pro-inflammatory cytokines, specifically IL-1b, TNF-a, IFN-a, and IFN-g [45]. FGL2was reported as a novel effector molecule in the immunoregulation of Treg cells [46].…”
Section: Discussionmentioning
confidence: 97%
“…Their self-renewal, multilineage differentiation capacity and immunomodulatory abilities make mesenchymal stromal cells (MSCs) promising tools for different therapeutic applications. According to their origin, MSCs may share some characteristics (Hoogduijn et al 2010) but may also present functional differences related to distinct gene and protein profiles (Busser et al 2015;Fayyad-Kazan et al 2017). The umbilical cord is becoming an important alternative source of MSCs (Davies et al 2017).…”
Section: Discussionmentioning
confidence: 99%